LITERATURE REVIEW: THE LAPS-HEURISTIC LEARNING MODEL AS AN INNOVATIVE APPROACH IN THE LEARNING PROCESS - Nasri (Formad English Foundation NTB-Jakarta, 2024)
This literature review explores the Logan Avenue Problem Solving (LAPS)-Heuristic learning model as an innovative approach in the learning process. The LAPS-Heuristic model focuses on student-centered problem-solving and aims to enhance critical thinking, cognitive development, and student engagement. The purpose of this review is to examine the key principles, effectiveness, and implementation challenges of the LAPS-Heuristic model. This research employed a literature review method to analyze and evaluate the laps-heuristic learning model as an innovative approach in the learning process. research stages are: 1) identification of literature sources; 2) data analysis and synthesis; data collection techniques are: 1) collection of secondary data; and 2) coding and categorization. data analysis techniques were 1) descriptive analysis; 2) comparative analysis; 3) synthesis of findings; and 4) validity and reliability. the last presentation of results. Three main findings emerged from the review: (1) The model significantly improves students' comprehension and retention of subject matter due to its emphasis on active engagement and systematic problem-solving. (2) It fosters higher-order thinking skills by encouraging students to analyze, evaluate, and synthesize information critically. (3) The model enhances problem-solving abilities by promoting systematic and creative approaches to tackling challenges. The findings is that the LAPS-Heuristic model can effectively prepare students for real-world challenges by developing a well-rounded set of cognitive, social, and practical skills. However, the review also identifies several limitations in implementing the model, including teacher readiness, resource constraints, and time requirements. Addressing these challenges is essential for the successful integration of the LAPS-Heuristic model in educational settings.